Model Penaggulangan Hiv/Aids Melalui Jejaring Antar Lembaga Berdasarkan Peraturan Daerah Kabupaten Malang Jawa Timur Nomor 14 Tahun 2008 - Mufidah Ch (An-Nisa' Journal of Gender Studies, 2016)
HIV/AIDS is spreading broader in society recently. Government and society have responded this issue by founding National commission for AIDS prevention (KPAN). Malang regency has issued local regulation Number 14 year 2008 on AIDS prevention, founding National commission for AIDS prevention (KPAN) which is facilitated by local governmental budget and building international cooperation. As the irony of the fact, the number of infected people is growing. This research aims at desribing the implementation of HIV-AIDS prevention based on local regulation Number 14 year 2008. The result shows supporting factors of the implementation and its handicaps trough institutional network in Malang. By applying qualitative method trough interview, observation, documentation, this research reveals that prevention process of AIDS through networking is effective enough. As the a result, through this program, the service is getting better, qualified facilities are provided, KРА work performance networking and society's understanding on HIV-AIDS issue is growing by process that is supported by social capital and stakeholder solidarity although handicaps are still found.